Role of training session in improving the knowledge of blood transfusion practices among undergraduates- a hospital based study. (Journal of Pathology of Nepal, 2020)
Background: Blood is a vital and limited resource with a lifesaving therapeutic benefit.  Knowledge of standard transfusion practices to be followed is important in delivering quality transfusion services. The present study aims at assessing the knowledge of transfusion practices among undergraduate medical students, train them, and to assess the impact of this type of training sessions in improving the outcome.Materials and methods:  82 undergraduate MBBS students participated in the study. The students were asked to attempt a pre-test and a post-test questionnaire before and after the training program. The training session comprised of audiovisual lecture and handout material given to the participants. The mean scores, percentage of both the tests, and percentage of improvement in scores from pre to post-test were analyzed.Results: The mean score in the pre-test was 8.3 with a minimum score of 3 and a maximum of 13 out of 15. The post-test mean score was 10.7 with a minimum score of 6 and a maximum score of 14 out of 15, which was significantly high. The training program helped in the overall improvement of the knowledge in various aspects of blood transfusion like indications, cross-matching, shelf life, transfusion practices, and management of adverse reactions. The p-value obtained was 0.003 (